Toward reliable and accurate evaluation of polymer solar cells based on low band gap polymers. Issue 3 (26th November 2014) - Ye, Long; Zhou, Chengyue; Meng, Haifeng; Wu, Heng-Hsin; Lin, Chi-Ching; Liao, Hua-Hsien; Zhang, Shaoqing; Hou, Jianhui
Abstract : To accurately evaluate the power conversion efficiencies, a general set of procedures were provided for low band gap polymers. Abstract : Along with the advances in polymer solar cells (PSCs), the accurate evaluation of novel photovoltaic polymers with various band gaps is an important issue that should be concerned, as well as needs to be addressed at various research laboratories in the world. In this work, we have focused on PSCs by employing some of the most efficient and well-known low band gap (LBG) polymers, for instance, PBDTTT-C-T, PBDTBDD, PDPP3T, PTB7-Th, PSBTBT and PBDTTPD, and obtained the corresponding spectral-mismatch factors (MMFs) under various reference cell/solar simulator combinations. Generally, there still exists ±25% spectral error even for a simulator whose spectrum grade is labeled as AAA. The best way to accurately evaluate the power conversion efficiencies (PCEs) of LBG polymers is by choosing a combination of a spectral-matched-silicon-solar-cell (match to LBG polymer's spectral responsivity spectrum) and a Class AAA solar simulator. Furthermore, our results could provide guidance for the accurate measurements of organic molecules, perovskites, and related photovoltaic technologies.